The Role of Humor in Stress Management and Psychological Well-Being: Coping Strategies in High-Stress Populations - Malizal , Zelynda Zeinab (Yayasan Sinergi Kawula Muda, 2024)
Humor has been widely recognized as a critical coping strategy that enhances psychological well-being by alleviating stress, anxiety, and depressive symptoms. This study provides a comprehensive narrative review of existing literature on the role of humor in mental health, particularly in high-stress environments such as healthcare, caregiving, and social adaptation. A systematic literature search was conducted across PubMed, Scopus, Google Scholar, and CINAHL, focusing on peer-reviewed studies examining humor-based interventions, social support, and coping mechanisms. Findings indicate that humor positively impacts emotional resilience, workplace stress reduction, and patient care experiences. Healthcare workers, caregivers, and marginalized populations benefit significantly from humor’s psychological effects, particularly when combined with strong social support. However, systemic barriers such as mental health stigma, cultural variations, and economic constraints limit the widespread adoption of humor as an intervention strategy. Addressing these challenges requires tailored humor-based programs, workplace well-being policies, and culturally adaptive approaches. This review underscores the need for future research exploring humor’s long-term effectiveness and digital applications in mental health interventions. A greater emphasis on policy-driven initiatives can facilitate the integration of humor into clinical and community-based settings, ultimately improving psychological well-being across diverse populations.